Development and validation of a CHECKLIST of cost-generating activities for the municipal instance of the immunobiologicals conservation cold chain (Research, Society and Development, 2021)
Objective: to develop and validate a checklist of cost-generating activities in the immunobiologicals conservation cold chain at the municipal level. Method: This is a methodological study, with a quantitative approach, which used the modified e-Delphi method to validate the activities. Twenty-three judges participated, including doctors, masters and specialists working at state, regional and municipal health levels. The content validation index and Cronbach's alpha coefficient were calculated to analyze the internal consistency of the checklist. Results: The checklist consists of 7 activities in the Transport and Receiving component, 18 in the activities in the Storage and Handling component and 2 activities in the Supervision and Continuing Education component. Considering all components, the checklist's total content validation index was 92.3%. Total internal consistency obtained a Cronbach's alpha coefficient value of 0.9534. Conclusion: The study provides a checklist of cost-generating activities of the municipal instance of the FC for the conservation of immunobiologicals that are reliable and with valid content, which may be useful to managers in the decision-making process for the allocation of financial resources.